Do Nudges Reduce Borrowing and Consumer Confusion in the Credit Card Market?. (3rd May 2022) - Adams, Paul; Guttman‐Kenney, Benedict; Hayes, Lucy; Hunt, Stefan; Laibson, David; Stewart, Neil
Abstract : We study nudges that turn out to have precise null effects in reducing long‐run credit card debt. We test nudges across two field experiments covering 183, 441 UK cardholders. Our first experiment studies nudges added to monthly credit card statements. Our second experiment studies letters and email nudges (separate from monthly statements) sent to cardholders who signed up to automatically pay the minimum required payment. In a follow‐up survey to our second experiment, we find that 96% of respondents underestimate the time it would take to fully repay a debt if the cardholder made only the minimum required payment. The nudges reduce this confusion, but underestimation remains overwhelmingly common.